(untitled) (Journal SCIENCEVOLUTION, 2024)
The present research was developed in students of basic secondary education, in the Rodrigo Lara Bonilla Educational Institution of Neiva, Colombia, for teaching the creation of plane figures (quadrilaterals), using GeoGebra software, for which a practice was carried out with a sample of 20 seventh grade students, applying the development of a pre-test and post-test, with a difference of 8 months (before and after the application of the didactic strategy). As a result, it was determined that the application of the didactic guide does have a significant impact on the students’ learning level in the subject of geometry, specifically in the teaching of plane figures. Consequently, students increased the average number of correct answers from 3.85 to 6.45 and academic performance improved by 39% of correct answers to 65%. Therefore, it is recommended to implement Geogebra software to develop didactic strategies in educational institutions as part of the digital transformation process in basic secondary education.